Abortion Services Utilization at KAHS during COVID-19 Lockdown - Shah, Rajiv; Basnyat, Subi; Panta, Prem Prasad (Journal of Karnali Academy of Health Sciences, 2020)
Background: Accessibility to the contraception and safe abortion services has been severely compromised by the COVID-19 pandemic and ensuing lockdown measures. It has been estimated the most impacted population are the vulnerable female of lesser developed countries. So, by this study we want to know how the COVID-19 pandemic impacted abortion services utilization has at our center. Methods: This is a descriptive cross-sectional study conducted at Karnali Academy of Health Sciences. The data were collected from the hospital records of Maternal and Child Health clinic and maternity ward. Census sampling was used. Data entry were done in excel and analyzed using SPSS 16 version. Frequencies and percentages were used for descriptive analysis. Results: During the study period of nine months, a total of one hundred and ninety eight cases had come to the centre for safe abortion care services. During the non-lockdown period there were about 41 cases in the 4 months period, about 10.25 cases per month was. And in the lock down period there were about 157 women in 5 months, which was in average 31.4 cases per month. Conclusion: There was a sharp increase in the cases of abortion during the lockdown by about three times. So the concerned authority should specially focus on the contraceptive accessibility of the couples during the lockdown period. Also the services delivery related to the reproductive health should be kept in high priority and should be made available even during the lockdown.